2019
DOI: 10.1002/pen.25159
|View full text |Cite
|
Sign up to set email alerts
|

Synthesizing radiation‐hard polymer and copolymers usinglaccolmonomers extracted from lacquer treetoxicodendron succedaneavia cationic polymerization

Abstract: In recent years, lacquer chemistry stimulated more attention from the scientific community due to its environmental friendly applications. Additionally, the “laccol” possesses promising radiation resistance due to its highly crosslinked polymer network. In nature, lacquer polymerization is induced via enzymatic radical initiation. Herein, as a novel approach, lacquer polymer was synthesized via cationic polymerization with aluminum chloride‐ethyl acetate coinitiator. This approach was further improved by polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Urushiol, which accounts to 60-70% of the raw lacquer collected from natural resource-rich Rhus vernicifera, is a catechol derivative with a linear alkenyl group. 24 In general, researches have shown that catechol structures can generate semiquinone radicals under the action of enzymes, 25 air, 26 and some inorganic one-electron oxidants (ferric chloride, silver nitrate, copper sulfate, etc. ), [27][28][29][30] and quinone radicals are oxidatively coupled with polyphenols and then form a biphenyl structure.…”
Section: Preparation Of Pul/agnpsmentioning
confidence: 99%
“…Urushiol, which accounts to 60-70% of the raw lacquer collected from natural resource-rich Rhus vernicifera, is a catechol derivative with a linear alkenyl group. 24 In general, researches have shown that catechol structures can generate semiquinone radicals under the action of enzymes, 25 air, 26 and some inorganic one-electron oxidants (ferric chloride, silver nitrate, copper sulfate, etc. ), [27][28][29][30] and quinone radicals are oxidatively coupled with polyphenols and then form a biphenyl structure.…”
Section: Preparation Of Pul/agnpsmentioning
confidence: 99%
“…Laccol extraction, laccol polymer preparation, and initiator preparation were carried out according to the procedures published in our previous article . High pure food grade d ‐limonene was used as received without further purification.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the unsaturation of this C‐17 side chain, it is a potent candidate for cationic polymerization process. As described in our previously published article , laccol was successfully polymerized via cationic polymerization using AlCl 3 .EtOAc coinitiator. Further broadening the applicability of laccol in industrial environment, copolymerization of laccol with limonene via cationic polymerization was studied herein to develop radiation hard copolymers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, NMR spectroscopy is one of the most important analytical tools that has been used in several fields. These fields include structural biology [29][30][31][32][33][34][35][36][37][38], organic chemistry [39][40][41][42][43][44][45][46][47][48][49][50][51][52], polymer characterization [40,46,[53][54][55][56][57][58][59][60][61][62][63][64], inorganic chemistry [65][66][67][68][69][70][71][72][73][74][75], and physics [76][77][...…”
mentioning
confidence: 99%